The Effect of Transformational Leadership on Employee Job Satisfaction (Study at Madrasah Ibtidaiyah Assaidiyah Surabaya) - Muslih Muslih; Giyoto Giyoto; Imam Makruf; Sulaiha Annisyaroh (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The active role of leaders and leadership models that are in accordance with the needs of educational institutions are very much needed. Teachers and Employees have a desire to be led by certain people who have a clear vision of the goals, understand how to realize the goals and try to teach them. The role of the leader in a school or madrasa is expected to create a sense of fairness for employees; Characteristics of leaders affect the work climate in an educational institution. Leaders expected by school employees are leaders who are able to provide job satisfaction to employees. This study was designed to examine whether transformational leadership has a significant effect on job satisfaction. Using a sample at Madrasah Ibtidaiyah Assyaidiyah, data collection was carried out by distributing 64 questionnaires. Based on the simple linear regression analysis used, the results showed that transformational leadership had a significant positive effect on employee job satisfaction.